The Effect of Adding Corn Cob Inhibitor to Primer Paint as a Corrosion Retardant On Train Roofs (Mild Steel SS 400) - Akbar Zulkarnain; Edi Nyoto Setyo Marsusiadi; Achmad Sholih Zidni; Dadang Sanjaya Atmaja; Willy Artha Wirawan (Journal of Railway Transportation and Technology, 2026)
Corrosion is one of the main problems that can reduce the quality and service life of steel materials in the railway industry, especially on train roofs made of SS400 mild steel. This study aims to examine the effectiveness of adding natural inhibitors from corn cob ash to epoxy primer paint in inhibiting the rate of corrosion and increasing the adhesive strength of the paint. The inhibitor was made through a process of extracting silica from corn cob ash and mixing it into the primer paint at various concentrations. Fourier Transform Infra Red (FTIR) testing was used to identify the silica content in the inhibitor, while testing was carried out on the adhesive strength using an adhesion tester and the corrosion rate using the weight loss test method in HNO₃ solution. The results showed that the addition of corn cob ash inhibitor formed a protective layer on the metal surface, improved paint adhesion, and significantly reduced the corrosion rate. This study demonstrates that the use of agricultural waste such as corn cobs as a natural inhibitor is an innovative, economical, and environmentally friendly solution for controlling corrosion in steel materials in the railway industry.